EKSISTENSI TRADISI PENGANTIN SAHUR DALAM SUKU BANJAR DESA PULAU PALAS KABUPATEN INDRAGIRI HILIR (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract : Indragiri Hilir Regency has the distribution of the banjar tribe from the island of Kalimantan and natural geographical conditions that have similarities with the banjar tribe on the island of Borneo. One example of a tradition for the banjar tribe that has been going on for quite a long time in Riau is the tradition of